How dangerous are released terrorist prisoners and what is being done to manage this risk? - Silke, Andrew (Pool Reinsurance (PoolRe), 2022)
The past decade has seen a general increase in the number of people convicted for terrorism-related offences in England and Wales, with an accompanying rise in the number of terrorist prisoners. This year, between 90-100 terrorist prisoners will be considered for release in England and Wales and, if recent trends hold, approximately half of these prisoners will be released. Between 2013 and 2021, 443 terrorist prisoners were released,1averaging roughly 50 former prisoners back on the streets each year.